Effect of Nd3+ substitution for Bi3+ on the dielectric properties and conduction behavior of Aurivillius NdBi4Ti3FeO15 ceramics. Issue 25 (22nd February 2016) - Rehman, Fida; Jin, Hai-Bo; Wang, Lin; Tanver, Abbas; Su, De-Zhi; Li, Jing-Bo
Abstract : NdBi4 Ti3 FeO15 and Bi5 Ti3 FeO15 ceramics were prepared by solid state reaction. Abstract : NdBi4 Ti3 FeO15 and Bi5 Ti3 FeO15 ceramics were prepared by solid state reaction. The effect of Nd 3+ on dielectric and electrical properties was investigated in a wide range of frequencies and temperatures by dielectric/impedance spectroscopies. The combination of impedance and electric modulus analysis enabled the distinguishing of two relaxation behaviors that were assigned to originate from grains and grain boundaries. Kinetic analysis of temperature-dependent dielectric data was performed to probe the defect-related conduction. The results demonstrated that the Nd 3+ substitution for Bi 3+ significantly suppressed the conductivity and the ferroelectric transition temperature was decreased to ∼250 °C in NdBi4 Ti3 FeO15 .